Poetry and Horseplay in Sidney's Defence of Poesie. (31st December 2016) - Lazarus, Micha
The playful discussion of 'horsemanship' that opens Sir Philip Sidney's Defence of Poesie has been variously interpreted as a straightforward anecdote about the chivalric arts, or an oblique rhetorical flourish, or something in between. This essay suggests a new context for Sidney's exordium by focusing primarily on its affiliation to the genre of the 'Art of Poetry'. In Horace's Ars poetica and other classical, scholastic and Renaissance treatises, horse-men and other unnatural hybrids embody the tension between decorum and poetic liberty. Three major traditions inform this trope: by the Renaissance the centaur could be an allegory of reason's struggle with the passions, an emblem of the poetic imagination, or a figure for compositional hybridity associated, especially, with Lucianic satire. Reading Sidney in the light of these traditions, finally, this essay explores aspects of the centaur's significance in the Defence and the Arcadia, and suggests that this kind of attention to metaphor might provide a bridge between critical and creative modes of Renaissance poetic thought.